2017
DOI: 10.1111/cen.13426
|View full text |Cite
|
Sign up to set email alerts
|

Nulliparity is associated with subtle adverse metabolic outcomes in overweight/obese mothers and their offspring

Abstract: Infants born of nulliparous overweight and obese women appear to be exposed to a less favourable metabolic environment in utero, with evidence of subtle adverse metabolic outcomes at birth compared to infants of overweight/obese multiparous women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The remaining 83 studies were further evaluated based on full text, and 51 articles were excluded for wrong publication type ( n = 26) (i.e., systematic review, study protocol, cohort characteristics report, conference presentation, book), wrong study design ( n = 7), and wrong outcome ( n = 23) (i.e., ineligible infant measurements); 32 articles were included for evaluation. Of these, 13 were randomized controlled trials [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], 16 were single-arm cohort studies [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], and 3 were case-control studies [ 5 , 6 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 83 studies were further evaluated based on full text, and 51 articles were excluded for wrong publication type ( n = 26) (i.e., systematic review, study protocol, cohort characteristics report, conference presentation, book), wrong study design ( n = 7), and wrong outcome ( n = 23) (i.e., ineligible infant measurements); 32 articles were included for evaluation. Of these, 13 were randomized controlled trials [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], 16 were single-arm cohort studies [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], and 3 were case-control studies [ 5 , 6 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The overall risk of bias for randomized controlled trials was low to- moderate. Approximately 54% of the studies (7 of 13) were rated as having “some concerns” for the overall potential risk of bias [ 21 , 22 , 24 , 25 , 27 , 28 , 29 ] ( Figure 2 ). This rating was primarily due to the seven studies being rated as having “some concerns” in the performance risk of bias domain, which was assessed by rating deviations from the intended intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the underlying mechanism remains unexplained and requires further exploration. Seneviratne et al [12] have recently reported that nulliparous and multiparous women may confer subtle metabolic disadvantage in overweight and obese mothers and their offspring. In our study, nulliparous women and women with two live birth may have similar magnitude of association with CKD, although the associations were not statistical significant.…”
Section: Discussionmentioning
confidence: 99%
“…During fetal development, the hypothalamic-pituitary-adrenal axis is extremely susceptible to programming, and alterations in the expression and function of glucocorticoid receptors and major glucocorticoid regulatory enzymes are observed in those exposed to undernourishment in early life[ 54 ]. Other factors associated with fetal programming include maternal exposure to endocrine disruptors, maternal infection and smoking and nulliparity[ 17 , 55 ]. Nulliparity is potentially associated with subtle adverse metabolic outcomes in overweight/obese mothers and their offspring, through uterine constraint effects[ 55 ].…”
Section: Factors Predisposing To Developmental Programming Of Obesity...mentioning
confidence: 99%